Upcycled Cocoa Pod Husk: A Sustainable Source of Phenol and Polyphenol Ingredients for Skin Hydration, Whitening, and Anti-Aging - Aknarin Anatachodwanit; Setinee Chanpirom; Thapakorn Tree-Udom; Sunsiri Kitthaweesinpoon; Sudarat Jiamphun; Ongon Aryuwat; Cholpisut Tantapakul; Maria Pilar Vinardell; Tawanun Sripisut (Life)
Theobroma cacao L. (cocoa) pod husk, a byproduct of the chocolate industry, has potential for commercial applications due to its bioactive compounds. This study aimed to determine the phytochemical composition, biological activity, and clinical efficacy of a standardized extract. This study compared 80% ethanol (CE) and 80% ethanol acidified (CEA) as extraction solvents. The result indicated that CEA yielded higher total phenolic content (170.98 ± 7.41 mg GAE/g extract) and total flavonoid content (3.91 ± 0.27 mg QE/g extract) than CE. Liquid chromatography–tandem mass spectrometry (LC/MS/MS) identified various phenolic and flavonoid compounds. CEA demonstrated stronger anti-oxidant (IC50 = 5.83 ± 0.11 μg/mL in the DPPH assay and 234.17 ± 4.01 mg AAE/g extract in the FRAP assay) compared to CE. Additionally, CEA exhibited anti-tyrosinase (IC50 = 9.51 ± 0.01 mg/mL), anti-glycation (IC50 = 62.32 ± 0.18 µg/mL), and anti-collagenase (IC50 = 0.43 ± 0.01 mg/mL), nitric oxide (NO) production inhibitory (IC50 = 62.68 μg/mL) activities, without causing toxicity to cells. A formulated lotion containing CEA (0.01–1.0% w/w) demonstrated stability over six heating–cooling cycles. A clinical study with 30 volunteers showed no skin irritation. The 1.0% w/w formulation (F4) improved skin hydration (+52.48%), reduced transepidermal water loss (−7.73%), and decreased melanin index (−9.10%) after 4 weeks of application. These findings suggest cocoa pod husk extract as a promising active ingredient for skin hydrating and lightening formulation. Nevertheless, further long-term studies are necessary to evaluate its efficacy in anti-aging treatments.